Beliefs and Attitudes of Medical Students from Public and Private Universities in Malaysia towards Individuals with HIV/AIDS - Koh Kwee Choy; Teh Jae Rene; Saad Ahmed Khan (The Scientific World Journal)
We describe the findings from a survey assessing the beliefs regarding testing, confidentiality, disclosure, and environment of care and attitudes towards care of people with HIV/AIDS (PLHWA), in 1020, 4th and 5th year medical students, from public and private medical universities in Malaysia. A self-administered validated questionnaire based on the UNAIDS Model Questionnaire with a 5-point Likert scale (5, strongly disagree; 4, disagree; 3, neutral; 2, agree; 1, strongly agree) was used as a survey tool. The survey included demographic data and data on undergraduate training received on HIV/AIDS. Statistical significance in the demographic data and training received by respondents was evaluated using the chi-square test while the independent Student’s t-test was used for comparison of means between public and private universities. A value of <0.05 was considered statistically significant with 95% confidence interval. Our study revealed less than 20% of medical students received adequate training to care for PLHWA. They had prevalent negative beliefs regarding testing, confidentiality, disclosure and environment of care towards PLHWA although in giving care to PLHWA, their attitudes were largely positive and nondiscriminatory.